A case report of perforated gall bladder in an adolescent female: a diagnostic dilemma successfully managed by laparoscopy - Garg, Ashish; Pandey, Srijan; Pusuluri, Rahul; Mohammad, Benazeer H.; Manju; Rishu (International Surgery Journal, 2024)
Gall bladder perforations are rare and usually seen in elderly age group having comorbidities like diabetes and are associated with severe morbidity and mortality. Gall bladder perforation is much rarer in younger patients and thus leads to diagnostic dilemma. These cases generally require exploratory laparotomy and are associated with high incidences of SSI. With advent of minimal invasive procedure laparoscopic cholecystectomy is an option for management with prompt and accurate diagnosis. We present a case of 19-year-old female with anaemia having severe pain in abdomen and fever at presentation. She was diagnosed as gall bladder perforation on ultrasound which was confirmed by CECT Abdomen. Patient was managed by laparoscopic subtotal cholecystectomy with uneventful post-operative period. Gall bladder perforations are rarely seen in young adults posing diagnostic dilemma. Delay in diagnosis can lead to increased morbidity and mortality. In patients of cholecystitis with non-resolving fever and peritonitis generalised or localised should raise a high suspicion of perforation and should be promptly diagnosed with CECT Abdomen. Although conventionally exploratory laparotomy is done for gall bladder perforation with peritonitis, diagnostic laparoscopy with cholecystectomy is a feasible option in selected patients. In young adults with non-resolving acute abdomen with calculous cholecystitis high degree of suspicion of Gall Bladder perforation should be kept. Laparoscopic cholecystectomy is a feasible option with minimal morbidity and higher cosmesis in young adults.